Revision of the Donald T. Kowalski’s collections of Lamproderma (Myxomycetes, Amoebozoa) reveals twice higher species diversity - Ronikier, Anna (Phytotaxa, 2022)
Donald T. Kowalski’s herbarium collection gathered in 1960s is among the most important historical documentation of nivicolous myxomycete diversity in North America. A revision of speciose genus Lamproderma from this collection deposited in UC was undertaken. Based on examination of 95 specimens that were originally classified by Kowalski into 13 species, 25 species have been recognized. The identity of seven species: L. arcyrionema, L. biasperosporum, L. columbinum, L. disseminatum, L. echinosporum, L. maculatum, and L. scintillans was confirmed and all specimens represented the species as originally determined by Kowalski. Remaining 18 species were either differently interpreted or not distinguished by Kowalski. The most interesting of them is a single collection of Diacheopsis sp. that most likely belongs to an undescribed species. Attempts to obtain molecular barcode reference sequences from Kowalski’s specimens failed, likely due to the degradation of DNA induced by chemical treatment of collections in the past, thus this material remains available only for morphological comparisons. Results of the present revision contribute to more adequate estimation of diversity of Lamproderma species in the USA revealing a much higher number of species than originally reported. More generally, these results emphasize a need of revisions of old collections what is particularly important in the genera like Lamproderma where taxonomic changes proposed during last decades made older published records unequivocal or difficult to interpret.